Home parenteral nutrition provision modalities for chronic intestinal failure in adult patients: An international survey. Issue 2 (February 2020) - Pironi, Loris; Steiger, Ezra; Brandt, Chrisoffer; Joly, Francisca; Wanten, Geert; Chambrier, Cecile; Aimasso, Umberto; Sasdelli, Anna Simona; Zeraschi, Sarah; Kelly, Darlene; Szczepanek, Kinga; Jukes, Amelia; et al.
Summary: Background & aims: The safety and effectiveness of a home parenteral nutrition (HPN) program depends both on the expertise and the management approach of the HPN center. We aimed to evaluate both the approaches of different international HPN-centers in their provision of HPN and the types of intravenous supplementation (IVS)-admixtures prescribed to patients with chronic intestinal failure (CIF). Methods: In March 2015, 65 centers from 22 countries enrolled 3239 patients (benign disease 90.1%, malignant disease 9.9%), recording the patient, CIF and HPN characteristics in a structured database. The HPN-provider was categorized as health care system local pharmacy (LP) or independent home care company (HCC). The IVS-admixture was categorized as fluids and electrolytes alone (FE) or parenteral nutrition, either commercially premixed (PA) or customized to the individual patient (CA), alone or plus extra FE (PAFE or CAFE). Doctors of HPN centers were responsible for the IVS prescriptions. Results: HCC (66%) was the most common HPN provider, with no difference noted between benign-CIF and malignant-CIF. LP was the main modality in 11 countries; HCC prevailed in 4 European countries: Israel, USA, South America and Oceania (p < 0.001). IVS-admixture comprised: FE 10%, PA 17%, PAFE 17%, CA 38%, CAFE 18%. PA and PAFE prevailed in malignant-CIF while CA and CAFE use was greater in benign-CIF (p < 0.001). PA + PAFE prevailed in those countries where LP was the main HPN-provider and CA + CAFE prevailed where the main HPN-provider was HCC (p < 0.001). Conclusions: This is the first study to demonstrate that HPN provision and the IVS-admixture differ greatly among countries, among HPN centers and between benign-CIF and cancer-CIF. As both HPN provider and IVS-admixture types may play a role in the safety and effectiveness of HPN therapy, criteria to homogenize HPN programs are needed so that patients can have equal access to optimal CIF care.